Análise da condição periodontal e traço de ansiedade de mulheres no periodo pós-parto - Souza, Rodrigo Zonatto de (2020)
Pregnancy is an important stage in the life of all women with substantial anatomical, physiological and emotional changes that’s could impact periodontal health. The main goal of this study was to evaluate if anxiety experienced by women in the postpartum period may contribute to the deterioration of periodontal health. This cross-sectional study was conducted with women recruited at the baby clinic at Positivo University, and the Specialty Dentistry Center (CEO) located at the University, Curitiba, Brazil. Data referring to the general characterization of the women were collected through a selfreported questionnaire. The anxiety was assessed according to the State-Trait Anxiety Inventory (STAI). Clinical examination was carried out according to the World Health Organization for oral health surveys. In the periodontal analysis, the plaque index (PI), probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BOP) were evaluated according to the classification established by the American Academy of Periodontology. Data for all patients included in the study were tabulated using Microsoft Excel for Windows 2013 and analyzed using the Graph Pad Prism 8.0 statistical program (Graph-Pad Software Inc., San Diego, CA) (p <0.05). 37 women were evaluated (mean age 31.9; ±7 years), mothers of children aged ranged from 9 to 48 months old, both genders. Data referring showed that most women have gingivitis and moderate anxiety but with a weak correlation between periodontal clinical parameters and STAI-T (coefficient r < 0.30; p> 0.05). This study provides evidence that maternal anxiety in the postpartum period was associated with gingival inflammation that we assumed that it is a transitory and reversible condition.